Skewed X inactivation is associated with phenotype in a female with adrenal hypoplasia congenita. Issue 9 (1st September 2008) - Shaikh, M G; Boyes, L; Kingston, H; Collins, R; Besley, G T N; Padmakumar, B; Ismayl, O; Hughes, I; Hall, C M; Hellerud, C; Achermann, J C; Clayton, P E
Abstract : Adrenal hypoplasia congenita (AHC) can occur due to deletions or mutations in the DAX 1 ( NR0B1 ) gene on the X chromosome (OMIM 300200). This form of AHC is therefore predominantly seen in boys. Deletion of the DAX 1 gene can also be part of a larger contiguous deletion including the centromeric dystrophin and glycerol kinase (GK) genes. We report a girl with a de novo deletion at Xp21.2 on the maternal chromosome, including DAX1, the GK gene and 3′ end of the dystrophin gene, who presented with salt losing adrenal insufficiency and moderate developmental delay, but relatively mild features of muscular dystrophy. Investigation using the androgen receptor as a marker gene identified skewed inactivation of the X chromosome. In the patient's leucocytes, the paternal X chromosome was completely inactive, but in muscle 20% of the active chromosomes were of paternal origin. Thus skewed X inactivation (deletion on the active maternal X chromosome with an inactive paternal X chromosome) is associated with AHC in a female. Variability in X inactivation between tissues may account for the pronounced salt loss and adrenal insufficiency but mild muscular dystrophy.